2002
DOI: 10.1111/j.1749-6632.2002.tb04102.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of RET Activation in Human Cancer

Abstract: Mutations that produce oncogenes with dominant gain of function target receptor protein tyrosine kinases (PTKs) in cancer and confer uncontrolled proliferation, impaired differentiation, or unrestrained survival to the cancer cell. However, insufficient PTK signaling may be responsible for developmental diseases. Gain of function of the RET receptor PTK is associated with human cancer. At the germline level, point mutations of RET are responsible for multiple endocrine neoplasia type 2 (MEN2A, MEN2B, and FMTC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(98 citation statements)
references
References 11 publications
(14 reference statements)
2
89
1
6
Order By: Relevance
“…Two novel mutations were identified in exon 11 of the RET proto-oncogene, in two sporadic MTC cases: a heterozygous point mutation at codon 630 (Cys630Gly), and a 18 bp deletion at nucleotide c.1881 associated in the same allele with a silent nucleotide substitution at codon 634 (Cys634Cys). Both mutations are located in the cysteine-rich domain coding sequence, which, when mutated, has been shown to constitutively activate RET (Santoro et al, 1995(Santoro et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Two novel mutations were identified in exon 11 of the RET proto-oncogene, in two sporadic MTC cases: a heterozygous point mutation at codon 630 (Cys630Gly), and a 18 bp deletion at nucleotide c.1881 associated in the same allele with a silent nucleotide substitution at codon 634 (Cys634Cys). Both mutations are located in the cysteine-rich domain coding sequence, which, when mutated, has been shown to constitutively activate RET (Santoro et al, 1995(Santoro et al, , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…This approach was tested recently by combined use of BRAF mutation with RET/PTC ), a process which did indeed improve the diagnostic sensitivity. However, the diagnostic specificity of this approach needs to be further investigated on large studies as RET/PTC is sometimes found in benign thyroid tumors (Nikiforov 2002, Santoro et al 2002, Tallini 2002. Combined use of BRAF mutation with Ras mutation in conjunction with FNAB to diagnose thyroid cancer is also being investigated (Baloch et al 2004), but a similar diagnostic specificity limitation also potentially exists as Ras mutations are also frequently seen in benign thyroid neoplasms (Tallini 2002, Vasko et al 2003.…”
Section: The Diagnostic Value Of Braf Mutation In Thyroid Cancermentioning
confidence: 99%
“…Thyroid cancer harbors several highly prevalent genetic alterations, some of which are seen only in this cancer. The classical oncogenic genetic alterations commonly seen in thyroid cancer include Ras mutations (Fagin 2002, Bongarzone & Pierotti 2003, RET/ PTC rearrangements (Nikiforov 2002, Santoro et al 2002, Tallini 2002, and PAX8-peroxisome proliferator-activated receptor g (PPARg) fusion oncogene (Kroll et al 2000. Various activating Ras mutations, widely seen in other cancers as well, occur mainly in FTC and the follicular variant of PTC (Vasko et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Chromosomal rearrangements linking the promoter and N-terminal domains of unrelated genes to the C-terminal fragment of RET result in the aberrant production of a chimeric form of the receptor in thyroid cells that is constitutively active. 17 Several forms have been identified that differ according to the 5 0 partner gene involved in the rearrangement, with RET/PTC1 and RET/PTC3 being the most common accounting for 490% of all rearrangements. 18 BRAF represent one type of RAF serine/threonine kinases that play a central role in the transduction of signals along the RAS-RAF-MAPK pathway regulat-ing cell growth, differentiation, and apoptosis in response to cytokines, hormones, and growth factors.…”
mentioning
confidence: 99%